Application of Data Mining Technology in Digital Museum - Song, Yongjia (International Journal of Computer Science and Information Technology, 2024)
The emergence of data mining technology has adapted to the needs of museums in the current era. This article briefly analyses the significance of digital museums and the application and shortcomings of data mining technology in museum digitization.